Poglavje iz zgodovine Ljubljanskega zvona: urednik Anton Ocvirk - Smolej, Tone (Slavistična revija, 2006)
The author examines the era from the end of 1933 to February 1935, when the eminent journal Ljubljanski zvon was edited by Anton Ocvirk. He seeks to reconstruct his editorship with previously mainly unknown correspondence material.
Keywords: editorship; Ljubljanski zvon; Ocvirk, Anton; Slovene literary magazins; slovenske literarne revije; uredniki